ANALISIS STATISTIKA FREKUENSI SURAT MASUK DAN KELUAR KANTOR KECAMATAN TABIR LINTAS MERANGIN - Dini Sukma Lestari; Sugeng Riyadi; Awatif; Hasmawati; Muhammad Jainuri (Hira Institute, 2026)
This study sims to statistically analyze the frequency of incoming and outgoing mail at the Office of Tabir Lintas Merangin Sub-district from June to August 2025. Using a quantitative descriptive method, primary data were collected from the official mail logbook and analyzed using descriptive statistics. The results show a consistent declining trend in both incoming (16,14,12) and outgoing (35,32,25) mail frequencies over the three-month period. The study finds that volume of outgoing mail is consistenly higher than incoming, indicating a high level of administrative productivity. Based on these findings, this study recomemends the implementation of a digital mail management system to improve efficiency and facilitate future data-driven decision-making.